(untitled) (Research, Society and Development, 2024)
Alzheimer’s disease (AD) is a devastating neurodegenerative condition that affects millions of people worldwide, presenting progressive cognitive deficits, functional impairment, and behavioral changes. In recent years, the role of glial cells in the pathogenesis and progression of AD has been increasingly recognized. Astrocytes, microglia, and oligodendrocytes, essential cells of the central nervous system, play fundamental roles in regulating the neural environment and responding to pathological stimuli. However, their dysfunction is implicated in neuroinflammation, neuronal loss, and progression of AD symptoms. This literature review aims to critically evaluate the influence of glial cells on the pathogenesis and progression of AD, using a rigorous and systematic approach over the past 20 years, drawing from primary studies including clinical trials, meta-analyses, randomized clinical trials, and systematic reviews. Additionally, innovative therapeutic strategies targeting astrocytes and microglia, such as immunotherapies, have been presented and analyzed, showing potential in reducing beta-amyloid burden and improving cognitive outcomes in animal models of AD. However, significant challenges such as glial cell heterogeneity and the need for more specific biomarkers need to be overcome to translate these advances into clinical practice. In summary, this review highlights the critical role of glial cells in AD pathogenesis and identifies essential areas of future research for the development of more effective and personalized therapies for this neurodegenerative disease.